Paleoalterações e cimentações nos depósitos continentais terciários de Portugal central: importância na interpretação de processos antigos - Cunha, Pedro Proença (2010)
This paper describes the palaeoweathering, cementation, clay minerals association and other closely related characteristics of central Portugal allostratigraphic Tertiary units (SLD's), that can be used for palaeoclimatic interpretation and palaeoenvironmental reconstruction. Lateral and vertical changes in palaeosols are of value for improving our understanding of the autocyclic and allocyclic controls on sediment acumulation in an alluvial basin, but they can also have stratigraphic importance. In some cases it is concluded that the geomorphological setting may have been more decisive than climatic conditions to the production of the palaeoweathering. During late Palaeogene (SLD7-8), surface and near-surface silicification were developed on tectonically stable land surfaces of minimal local relief under a semi-arid climate; groundwater flow was responsible for some eodiagenesis calcareous accumulations, with the neoformation of palygorskite. Conditions during the Miocene (SLD9-11) were favourable for the smectization of the metamorphic basement and arenization of granites. Intense rubefaction associated with basement conversion into clay (illite and kaolinite), is ascribed to internal drainage during late Messinian-Zanclean (SLD12). During Piacenzian (SLD13) intense kaolinization and hydromorphism are typical, reflecting a more humid and hot temperate climate and important Atlantic fluvial drainage. Later on (Gelasian-early Pleistocene ?; SLD14). more cold and dry conditicns are interpreted, at the beginning of the fluvial incision sage. Silica cementation is identified in the upper Eocence-Oligocene ? (SLD18; the major period of silicification), middle to upper Miocene (SLD10)and upper Tortonian-Messinian (SLD11); these occurrences are compatible with either arid or semi-arid conditions and the establishment of a flat landscape upon which a silcrete was developed.